2017
DOI: 10.3386/w23485
|View full text |Cite
|
Sign up to set email alerts
|

Cyclical Job Ladders by Firm Size and Firm Wage

Abstract: the merged paper. Any opinions and conclusions expressed herein are those of the authors and do not necessarily represent the views of the U.S. Census Bureau. All results have been reviewed to ensure that no confidential information is disclosed. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
76
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(86 citation statements)
references
References 2 publications
10
76
0
Order By: Relevance
“…They show that the gross poaching inflow share is increasing in size. Haltiwanger et al (2017) challenge these findings based on their stronger net poaching test. They work with administrative data from the LEHD, whose geographical coverage of private sector employers increased over time and recently completed.…”
Section: Firm Sizementioning
confidence: 99%
See 1 more Smart Citation
“…They show that the gross poaching inflow share is increasing in size. Haltiwanger et al (2017) challenge these findings based on their stronger net poaching test. They work with administrative data from the LEHD, whose geographical coverage of private sector employers increased over time and recently completed.…”
Section: Firm Sizementioning
confidence: 99%
“…A stronger test of a common ranking of jobs also takes into account retention. Net poaching, first proposed and implemented by Haltiwanger et al (2017) as a refinement of Moscarini and Postel-Vinay (2009)'s gross poaching inflow share, is the difference between the hiring into and separations from a given job type that only involve job-to-job quits. In practice, this measure can be applied to a firm, as the number of workers hired by that firm who are currently employed at other firms minus the number of own employees who quit directly to other firms, both normalized by that firm's size.…”
Section: Ranking Jobsmentioning
confidence: 99%
“…Job mobility is considered an important source of career advancementmeasured by wage increasesat least since Topel and Ward (1992). More recently, Haltiwanger et al (2017) found that worker mobility in the United States across jobs typically follows an upward trend in the between-firm wage hierarchy, thereby functioning as a major mechanism of upward wage mobility. In addition, firms become increasingly important in determining a worker's wage (Barth et al (2016) provide empirical evidence for the United States).…”
Section: Previous Empirical Evidencementioning
confidence: 99%
“…63 Haltiwanger, Hyatt, Kahn and McEntarfer (2017) show that workers matching to jobs in downturns are more likely to match to low-paying rms than high-paying rms.…”
mentioning
confidence: 99%